A vasutak kiépülése a Bánságban - Majdán, János (Közép-Európai Közlemények, 2010)
Until the 1850s in the three counties on the territory of the Bánság the traffic only could be arranged on the Tisza and Maros rivers and on the roads of very low quality. A company named Austrian National Railways built the first line in the 1850ies. In addition to the 581 kilometre long line of the private company, fifteen territorial firms had built lines altogether 1378 kilometres long. In fifty years one of the thickest railway networks was built in the Bánság and it became a part of the Hungarian State Railways after the January of 1891.